A Complexity of Kiswahili Pairwise of Verbal Extensions: Algorithmic Approach - Simon, Chípanda Serikal; Pembe, Hilda (Machakos University, 2018)
The paper describes semantics architecture of morph pairwise in Kiswahili verbal extensions. Kiswahili morphology is well documented, though semantic descriptions of these morphs are ignored and the theory for handling them. For instance some verb morphs are silent semantically though morphologically exhibit i:e the verb wa-sh-i-k-a ‘burnable’ in Swahili language is difficult to explain the sense and its constituents, and most of the speakers and writers generalize such verbalizers senses and ignoring each constuent’s sense such behavior needs to be described at length and the way of handling them theoretically. Cognitive Grammar was the theory applied for data analysis. The theory describes that meaning can be figured out basing on not only by word constituencies but context and experiences of the language users. The technique for data collection was documentary reviews of which 5 sources were reviewed to see how such derivations have been generalized semantically against algorithm architecture then depicting the generalized data for more algorithm analysis. It was found that, a step by stem derivations may make us understand the silent semantics of verbal morphs and their implicit senses other than generalizing them. Thus since Kiswahili is becoming a global language and East African in specific, its grammar should be well identified.
Keywords: Kiswahili; verbal extensions; semantic architecture